2018
DOI: 10.1177/0269216318773956
|View full text |Cite
|
Sign up to set email alerts
|

In silico (computed) modelling of doses and dosing regimens associated with morphine levels above international legal driving limits

Abstract: Background:Morphine can cause central nervous system side effects which impair driving skills. The legal blood morphine concentration limit for driving is 20 µg/L in France/Poland/Netherlands and 80 µg/L in England/Wales. There is no guidance as to the morphine dose leading to this concentration.Aim:The in silico (computed) relationship of oral morphine dose and plasma concentration was modelled to provide dose estimates for a morphine plasma concentration above 20 and 80 µg/L in different patient groups.Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The results showed that the 90% confidence intervals for geometric mean ratios were within standard bioequivalence boundaries for all other pharmacokinetic parameters, indicating that both tablet formulations were located in the accepted bioequivalence criteria compared with the oral solution (Ye et al, 2018 ). Boland et al ( 2018 ) used SIMCYP to generate a dose-concentration model by using data from different genders, ages, and oral morphine formulations. The model was then validated against clinical pharmacokinetics data and used to calculate the association of the morphine dose with the plasma concentration.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the 90% confidence intervals for geometric mean ratios were within standard bioequivalence boundaries for all other pharmacokinetic parameters, indicating that both tablet formulations were located in the accepted bioequivalence criteria compared with the oral solution (Ye et al, 2018 ). Boland et al ( 2018 ) used SIMCYP to generate a dose-concentration model by using data from different genders, ages, and oral morphine formulations. The model was then validated against clinical pharmacokinetics data and used to calculate the association of the morphine dose with the plasma concentration.…”
Section: Applicationsmentioning
confidence: 99%
“…The model was then validated against clinical pharmacokinetics data and used to calculate the association of the morphine dose with the plasma concentration. Finally, the analysis showed that older age, female sex, modified-release formulation, and inferior renal function were related to higher plasma concentrations (Boland et al, 2018 ). This result can help clinicians provide personalized prescription decisions.…”
Section: Applicationsmentioning
confidence: 99%
“…[46] The relation between breathlessness and driving performance whist on opioids must also be explored as current legal morphine limits for driving (where imposed) are far higher than the doses used in this study. [13]…”
Section: Main Findingsmentioning
confidence: 99%
“…Regular, low-dose (≤30mg/day), [13] sustained-release morphine safely reduces chronic breathlessness in people with COPD. [14,15] Recently, low-dose, sustained-release morphine has been approved by regulatory bodies in Australia for the treatment of chronic breathlessness.…”
Section: Introductionmentioning
confidence: 99%
“…The Royal College of Anaesthetists states that doses of about 200 mg day À1 could be as dangerous as having borderline illegal driving blood alcohol levels. 2 In fact, the clear desensitization of opioid receptors may cause methadone to intervene in impacts started by morphine, and in its continual presence, may even interrupt the cascade of cellular episodes and avoid lengthy neuro-chemical modications due to the chronic exposure to morphine. 3 One of the studies reported methadone as a synthetic analgesic drug with widespread utilization for treating opioid dependence since the mid-1960s.…”
Section: Introductionmentioning
confidence: 99%